Global Collaborative Advantage Efforts Toward Decolonization of Business Ethics and Management Scholarship. - Mahsud, R.
The current trend of prescribing and enforcing ethical business constructs, models, and frameworks developed in and by the Global North has become a new form of paternalistic colonizing of the Global South. Such behavior dangerously mirrors historically oppressive movements through colonization and continues extractive and damaging practices. Indeed, the enforcement of Northern constructs, models, and frameworks facilitates the maintenance of an artificial global hierarchy which continues to harm the South to the North?s benefit. They overlook and prohibit any possible inclusion of ethical and philosophical frameworks derived from the wisdoms and traditions of the South. This article advances the goal of Global Collaborative Advantage or GCA, which utilizes a decolonizing perspective within the field of business ethics and strives for a stronger incorporation of diverse sources of wisdom from the Global South. GCA calls for a South-led thought and action process, bringing the world?s wisdom traditions together while it de-centers Euro-originated perspectives and centers those from the South. It offers a model of relational exchange in markets for business organizations rather than the current transactional-exchange-focused system, and calls for a truth and reconciliation process, among other recommendations. This article thus makes the case for developing a model that draws from a variety of global perspectives on humanity, society, and economics to broaden the possibilities for ethical, meaningful, and generative exchange in global markets.